Cryptic speciation in Southern Ocean Aequiyoldia eightsii (Jay, 1839): Mio-Pliocene trans-Drake Passage separation and diversification - Gonzalez-Wevar, Claudio A.; Gerard, Karin Francoise; Rosenfeld, Sebastian; Saucede, Thomas; Naretto, Javier; Diaz, Angie; Morley, Simon A.; Brickle, Paul; Poulin, Elie (My University, 2019)
The species of the genus Aequiyoldia Soot-Ryen, 1951, previously known as Yoldia, are common, soft-substratum, sareptid bivalves. In the Southern Ocean, Aequiyoldia eightsii (Jay, 1839) was originally described from the Antarctic Peninsula and has also been reported in southern South America. The species A. woodwardi (Hanley, 1960) was reported for the Falkland/Malvinas Islands and Tierra del Fuego, but this taxon has been recently synonymised within the broadly distributed A. eightsii. Aequiyoldia has received little attention across its distribution in the Southern Ocean, and although its taxonomy and systematics remain uncertain, all the species have been grouped under a single and broadly distributed unit: A. eightsii. Nevertheless, preliminary mtDNA comparisons demonstrated a marked genetic divergence ( > 7%) between A. eightsii populations from South America and Antarctic Peninsula. In order to further understand the diversity and biogeography of Aequiyoldia, we analyzed A. eightsii populations from different provinces of the Southern Ocean including South America (SA), the Falldand/Malvinas Islands (FI), the Antarctic Peninsula (AP), and Kerguelen Islands (KI). Individuals were characterized according to typical diagnostic morphological measurements and phylogenetic relationships were reconstructed based on mtDNA (cytochrome c oxidase subunit I). Patterns of genetic divergence of nucDNA intergenic transcribed spacers (ITS1, ITS2) were also estimated. The statistical analysis of external diagnostic characteristics revealed two morphotypes: (1) individuals with the morphology recorded for the nominal FI species, A. woodwardi, and (2) individuals from SA, AP, and KI, with the morphology recorded for A. eightsii. However, phylogenetic reconstructions based on mtDNA and nucDNA suggest the presence of at least five lineages within A. eightsii including: one lineage in Kerguelen Island, two lineages in the Antarctic Peninsula, one lineage in South America, and the last one restricted to the Falkland/Malvinas Islands. Such results are evidence that the Antarctic Polar Front represents an historical biogeographic barrier for this group and that after the separation of these lineages, they followed independent evolutionary pathways in different provinces of the Southern Ocean. Estimates of divergence time suggest that KI separated from other Aequiyoldin lineages close to the middle Miocene. Following this, the separation between the AP and SA lineages occurred at the end of the Miocene around 7.5 Ma. Finally, Aequiyoldia diversified during the Pliocene in Antarctic Peninsula (similar to 4.5 Ma) and South America (similar to 3.0 Ma). Individuals from FI exhibited morphological differences, and 4% of divergence from South American individuals, suggesting that A. woordwardi could be revalidated. Similarly, the marked molecular divergence between the KI and the rest of the recorded lineages also support the validity of A. kerguelensis (Thiele, 1931).
Keywords: biogeography; southern ocean; antarctic-magellan connection; kerguelen islands; antarctic peninsula; south america; morphometry; systematics; phylogeny